ANTIDIABETES TEST OF ETANOL EXTRACT OF ARA SUNGSANG LEAVES (Asystasia gangetica L.) ON ALOKSAN INDUCED WHITE MICE - Saputri, Muharni; Fujiko, Muflihah; Dasopang, Eva Sartika; Arianti, Nova; Naswa, Shinta (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
Type 2 diabetes mellitus is caused by progressive impairment of insulin secretion leading to insulin resistance. Long-term use of antidiabetic drugs has gastrointestinal side effects as well as an increased risk of hypoglycemia. Therefore, a safer herbal treatment was developed. The purpose of the study was to determine the antidiabetic activity of ethanol extract of ara sungsang leaves on the reduction of glucose levels. The research is experimental, with the stages of making and standardizing simplisia, phytochemical screening, extraction, testing antidiabetic activity in vivo with 25 male mice. Blood glucose levels were determined at the beginning of fasting, after alloxan induction dose of 150 mg/kgbw, day 3, 6, 9, 12, 15. Blood glucose levels were analyzed statistically using the oneway ANOVA method. The results of the examination of simplisia standardization showed that the standardization of simplisia met the requirements. Phytochemical screening results showed that ara sungsang contains alkaloids, flavonoids, saponins, tannins, glycosides, and steroids/triterpenoids. The antidiabetic activity test in mice showed that the ethanol extract of ara sungsang at a dose of 225 mg/kgbw had a greater effect on reducing blood glucose levels than doses of 75 and 150 mg/kgbw.